Comparing percutaneous treatment and cholecystectomy outcomes in acute cholecystitis patients: a systematic review and meta-analysis - Gabriele Fanciulli; Giuliana Favara; Andrea Maugeri; Martina Barchitta; Antonella Agodi; Guido Basile (World Journal of Emergency Surgery)
Abstract Background Acute cholecystitis (AC) is a common and serious condition characterized by gallbladder inflammation, most often caused by cystic duct obstruction due to gallstones. Although laparoscopic cholecystectomy (CC) is the preferred surgical treatment, percutaneous cholecystostomy (PC) is frequently considered for high-risk surgical patients. The optimal management strategy for these patients remains a topic of debate. These systematic review and meta-analysis aim to provide an updated evaluation of studies comparing the clinical outcomes of AC patients treated with PC versus those undergoing CC, as well as the outcomes of CC alone versus PC followed by CC. Methods A literature search was carried out across Web of Science, Medline, Embase, and PubMed up to April 2024. Observational studies comparing patients undergoing PC versus CC, as well as CC versus PC followed by CC, and reporting mortality, morbidity, and readmission were included. Data extraction and quality assessment were independently performed by two reviewers, with bias risk evaluated using the Newcastle-Ottawa Quality Scale. The pooled odds ratio (OR) was obtained through meta-analyses by using STATA software (Version 18). Results A total of 27 studies were included, with 16 comparing PC versus CC and 11 assessing PC followed by CC versus CC alone. Meta-analyses revealed that CC was associated with significantly lower mortality (OR = 0.26; 95% CI = 0.14–0.48) and readmission rates (OR = 0.37; 95% CI = 0.18–0.75) compared to PC. The benefits of laparoscopic cholecystectomy over percutaneous cholecystostomy were particularly evident for mortality (OR = 0.17; 95% CI = 0.09–0.33), while a non-significant trend towards reduced readmission rates was also observed (OR = 0.28; 95% CI = 0.07–1.13). However, PC was identified as a viable alternative in high-risk surgical patients. Studies examining PC followed by CC versus CC alone showed diverse results, with some indicating reduced surgical complications and improved outcomes, while others reported no significant benefits. Conclusion This work highlights that CC is associated with better outcomes, including lower mortality and readmission rates, compared to both PC alone and PC followed by CC. The combined approach did not show a significant advantage over immediate CC. Further research with larger studies and standardized protocols is needed to refine treatment strategies for high-risk AC patients.